The impact of adopting social media in teaching and learning among it and non it student at higher learning institution - Ahmad, Amran; Mat Salleh, Mazuni (2016)
In reality, higher learning institutions are not fully benefitted from the adoption of social media in teaching and learning. Perhaps, most of them are relying on traditional lecture which is a face to face teaching methods. Moreover, the impact of adopting social media between IT and Non IT student is not clearly define. The purpose of this paper is to present a study on the adoption of social media as a medium in teaching and learning between IT and Non IT student. The questionnaire is used to collect a demographics, social media usage levels and social media adoption stages in teaching and learning among IT and Non IT students. The study found that there are no significant differences between IT and Non IT students in terms of the level of usage in teaching and learning.As a result, adopting social media at higher learning institutions should be easier and acceptable inteaching and learning.